Building China : Informal Work and the New Precariat - Swider, Sarah Christine (Book collections on Project MUSE., 2015)
Roughly 260 million workers in China have participated in a mass migration of peasants moving into the cities, and construction workers account for almost half of them. In Building China, Sarah Swider draws on her research in Beijing, Guangzhou, and Shanghai between 2004 and 2012, including living in an enclave, working on construction jobsites, and interviews with eighty-three migrants, managers, and labor contractors. This ethnography focuses on the lives, work, family, and social relations of construction workers. It adds to our understanding of China's new working class, the deepening rural-urban divide, and the growing number of undocumented migrants working outside the protection of labor laws and regulation. Swider shows how these migrants members of the global "precariat, " an emergent social force based on vulnerability, insecurity, and uncertainty are changing China's class structure and what this means for the prospects for an independent labor movement.--